JUDICIAL REVIEW OF POST-NUPTIAL AGREEMENT AFTER CONSTITUTIONAL COURT DECISION NUMBER 69/PUU-XIII/2015 - Hidayatullah, Syarif; Aidi, Zil (Universitas Muhammadiyah Ponorogo, 2023)
For the purpose of regulating the financial effects of their marriage, a husband and wife may enter into a prenuptial or postnuptial agreement. In light of Law No. 1 of 1974, the author seeks to clarify the effect of a postnuptial agreement and the subsequent status of the spouses' property. Juridically, the research is based on an approach to the principles of legal principles and rules relating to the applicable legislation, the Implementing Government Regulation of the Republic of Indonesia Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974, and the decision Number 69/PUU-XIII/2015 of the Constitutional Court of the Republic of Indonesia. Constitutional Court decision 69/PUU-XIII/2015 governs the process by which a husband and wife can enter into a marriage agreement after their wedding by using a District Court Decision.